Being Nuclear on a Budget: Churchill, Britain and "Atoms for Peace, " 1953–1955. Issue 4 (1st October 2016) - Theaker, Martin
ABSTRACT: This analysis critiques the impact of President Dwight Eisenhower's 1953 "Atoms for Peace" initiative on Washington's alliance with Britain, itself a newly crowned nuclear state. Prime Minister Winston Churchill's taste for personal diplomacy led him to support his friend's proposal without real consideration for how the contributions of fissionable materials and manpower demanded by the scheme would damage Britain's overstretched domestic nuclear project. Membership of an international atomic agency allowed Britain to reaffirm its global status whilst depleting the resources needed to develop its native technology. In turn, the article discusses the commercial challenge posed by American nuclear firms and highlights how reactor exports quickly became a contest between the quality of British research and the quantity of American subsidies. In this way, it establishes how "Atoms for Peace" prejudiced both Britain's domestic nuclear effort and export potential, in turn shedding light on Washington's relations with an ailing Great Power.